Information needs on nutrition in link to cancer prevention among cancer patients, high-risk individuals and general population – A national cross-sectional study. (April 2023) - Veron, L.; Chaltiel, D.; Raynard, B.; Rassy, N.; Scotté, F.; Charles, C.; Pons, M.; De Jesus, A.; Accolas, L Gueroult; Bergougnoux, A.; Caron, O.; Delaloge, S.
Summary: Background & aims: Nutrition is one of the fundamentals of cancer prevention. Knowing what are the patients' needs and beliefs in terms of "nutrition and cancer" information helps tailor future nutritional interventions. The aim of this study was to evaluate specific information needs about "nutrition in relation to cancer prevention", including primary and tertiary prevention, among cancer patients, cancer-free individuals, and genetic high cancer risk individuals. Methods: This online survey was shared within two large National cancer social networks and proposed to all attendees and carers of a comprehensive cancer center. Results: 2887 individuals answered the survey (of whom 33% were cancer patients, 13% high-risk individuals and 55% participants of the general population). More than 80% of participants were women, had at least a high school degree. Median body mass index was 23.2 kg/m 2 . Eleven percent (n = 321) were following a diet, mostly low carbohydrate and weight-loss diets. Around 70% of all categories felt they lacked information on nutrition and cancer interplays. Only 12% of cancer patients (n = 108) considered they had received enough information on nutrition during their care pathway. A majority of participants agreed that food can modify cancer risk (93%, n = 2526) and 66% (n = 1781) considered that nutrition should be personalized according to the risk of cancer. Only twenty-nine percent (n = 792) believed that eating 5 fruits and vegetables a day was enough to avoid cancer, but 64% (n = 1720) thought that dietary supplements could help obtain a better health. All proposed nutrition topics were considered important by the participants. Conclusions: Although cancer patients and cancer-free respondents, whether at high risk of cancer or not, share a common broad interest on the interplay between nutrition and cancer and seek after more information on this topic, some false beliefs are observed. Healthcare providers could successfully propose more evidence-based information to these populations. Highlights: Cancer patients and cancer-free people want more information on "nutrition and cancer". Beliefs about "nutrition and cancer" are sometimes false. Patients expect practitioners to meet their information needs.